2017
DOI: 10.1021/acs.langmuir.7b02038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adsorbed Alcohol Layers on the Behavior of Water Molecules Confined in a Graphene Nanoslit: A Molecular Dynamics Study

Abstract: With the rapid development of a two-dimensional (2D) nanomaterial, the confined liquid binary mixture has attracted increasing attention, which has significant potential in membrane separation. Alcohol/water is one of the most common systems in liquid-liquid separation. As one of the most focused systems, recent studies have found that ethanol molecules were preferentially adsorbed on the inner surface of the pore wall and formed an adsorbed ethanol layer under 2D nanoconfinement. To evaluate the effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…These results are consistent with another recent simulation study in which the adsorption of alcohol/water mixtures at a mole fraction of 5% in slit graphene pores 20 Å-wide is modeled using SPC/E water and OPLS-AA alcohol. 21 In that instance, an alcohol concentration close to 91% for the adsorbed methanol-water mixture was reported, in agreement with our findings. Note, however, that the study of Gao et al 21 is not directly comparable to ours since in their case the confined fluid is not in equilibrium with a liquid solution mediated by the corresponding vapor phase, i.e., it is not the result of an equilibrium adsorption process.…”
Section: Focusing Now On Methanol [Fig 2 (Bottom Panel)] Our Simulations Indicate That the Onset Adsorption Pressure Alsosupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with another recent simulation study in which the adsorption of alcohol/water mixtures at a mole fraction of 5% in slit graphene pores 20 Å-wide is modeled using SPC/E water and OPLS-AA alcohol. 21 In that instance, an alcohol concentration close to 91% for the adsorbed methanol-water mixture was reported, in agreement with our findings. Note, however, that the study of Gao et al 21 is not directly comparable to ours since in their case the confined fluid is not in equilibrium with a liquid solution mediated by the corresponding vapor phase, i.e., it is not the result of an equilibrium adsorption process.…”
Section: Focusing Now On Methanol [Fig 2 (Bottom Panel)] Our Simulations Indicate That the Onset Adsorption Pressure Alsosupporting
confidence: 92%
“…4 On the other hand, studies addressing the adsorption of alcohol and water/alcohol mixtures in simple geometries are comparatively more scarce, although the topic has gained some attention during the last few years. [17][18][19][20][21][22][23][24][25][26] Experiments of adsorption of pure methanol were carried out mainly in carbon black, activated carbon, or in crystalline carbon pores with hexagonal shape. [27][28][29] The adsorption in a simple slit geometry was investigated in a few simulation studies, which showed that adsorption occurs below bulk saturation pressure for pores narrower than 2 nm and that methanol forms chains for narrow pores, which are perturbed as the pore size increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It shows that the methane molecules could have a great slip velocity on the graphene surface, and such slip velocity could be up to 8.9 m/s, 16.3 m/s, and 28.6 m/s when the pore size is 5 nm, 10 nm, and 15 nm, respectively. Actually, in the slit-like graphene nanopore, such obvious surface slip velocity appears not only for CH 4 , but also in the flow of water, alkane, and some other geofluids [45,62,63]. The result also indicates that the pore size has nonnegligible effect on the slip velocity 5 Geofluids when CH 4 is confined in organic graphene nanopore.…”
Section: Resultsmentioning
confidence: 89%
“…To improve computational efficiency, we used coarse-grained particles to represent gases moving like particles with zero charge. Therefore, the effect of Coulomb interactions between the gases and the wall on the fluid transportation is ignored, and the effect of dangling and/or broken bonds is weak and also ignored here (Leggesse et al, 2016;Gao et al, 2017). A buffer distance of 2.5 Å is set between each pair of graphite fragments to allow relaxation of the sheets while preventing direct overlap.…”
Section: Rough Nanopore Simulation Setupmentioning
confidence: 99%